2017
DOI: 10.1007/s10973-017-6297-1
|View full text |Cite
|
Sign up to set email alerts
|

Physical structure and mechanical properties of polyamide/bamboo composites

Abstract: OATAO is an open access repository that collects the work of Toulouse researchers and makes it freely available over the web where possible.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 42 publications
2
13
0
Order By: Relevance
“…This continuity is analogous with the one observed on the composite when the filler is treated with a coupling agent . A previous study on polyamide matrix composites filled with bamboo flour showed that this kind of treatment is not necessary with the PA 11 composite due to the formation of hydrogen bonds between the polymer and the fibers …”
Section: Resultssupporting
confidence: 78%
See 1 more Smart Citation
“…This continuity is analogous with the one observed on the composite when the filler is treated with a coupling agent . A previous study on polyamide matrix composites filled with bamboo flour showed that this kind of treatment is not necessary with the PA 11 composite due to the formation of hydrogen bonds between the polymer and the fibers …”
Section: Resultssupporting
confidence: 78%
“…This study shows that the presence of bamboo fibers does not significantly modify the thermal behavior of the crystalline phase of PA 11 in PA 11/BF composites. The shape and magnitude of the melting peak of PA 11 are unmodified . Physical interactions in the amorphous phase of PA 11/BF composites inhibit the physical aging observed in the amorphous phase of bulk PA 11.…”
Section: Resultsmentioning
confidence: 99%
“…As an extension of wood-plastic composites (WPCs), bamboo-plastic composites (BPCs) are a kind of biomass-plastic mix that consists of a variety of components, including bamboo fibers (BFs) and thermoplastic materials (e.g., polyethylene, polypropylene, polyvinylchloride, etc.) [2][3][4]. BPCs are intriguing due to their promising features with regard to low density, good thermal insulation, and good mechanical properties.…”
Section: Introductionmentioning
confidence: 99%
“…Among various nanomaterials, halloysite nanotubes (HNTs) have been incorporated as a new type of green, unique, and promising reinforcing filler for thermosets and thermoplastic polymers [19][20][21]. HNTs (Al 2 Si 2 O 5 (OH) 4 •nH 2 O), a hydrated polymorph of 1:1 rolling phyllosilicate clay, are readily obtainable and biocompatible, providing great advantages compared with other traditional fillers such as carbon nanotubes [22,23]. HNTs can be readily dispersed in most polymer composites due to their rod-like geometry, low hydroxyl density on the surface, and lack of intertwining [24].…”
Section: Introductionmentioning
confidence: 99%
“…So far, a wide variety of surface modification techniques based on physical or chemical means have been developed by the industry and academia. [2][3][4][5][7][8][9][10][11][12][13] Among these methods, the main one is to add coupling agents or compatibilizers into the polymer matrix. For polyolefin composites, the most often used compatibilizers are maleic anhydride-grafted PE or PP.…”
Section: Introductionmentioning
confidence: 99%